ANALISIS NILAI EKONOMI KEBERADAAN WISATA ALAM DANAU SIAIS DI KABUPATEN TAPANULI SELATAN - Zulka Hidayati; Agus Purwoko; Ma’rifatin Zahra (Program studi Kehutanan USU, 2012)
This study aims to calculate the economic value of Lake Objects Nature Siais, Rianiate, Angkola District West, South Tapanuli using travel cost method, knowing the intensity of the visit and to determine the factors that affect the intensity of the visit. The number of samples used in this study were 100 respondents, while sampling using quota sampling technique. Based on research conducted obtain economic value of natural attractions of Lake Siais using travel cost method is for Rp.364.326.492, 6 /tahun. The intensity of tourist visits to Lake Siasis Nature is as much as one visit, while the factors affecting the intensity of the visit is the level of income and the time needed to tourism. Keywords: Natural Attractions: Lake Siais, economic value, the cost of travel, the intensity of the visit.